A review of the sampling methods used in aerial survey - Jolly, G.M. (International Livestock Centre for Africa, 1981)
Reviews procedures for obtaining reliable information on animal populations, other ecological features and land use generally from low-flying aircraft by direct observation or conventional photography, with reference to types of sampling unit, and the relative merits of unstratified systematic and stratified random sampling.